Key Catalysts of Agricultural Advancement in the state of Gujarat - Dr. Geetanjali Chauhan, (The Bioscan, 2024)
Purpose: The purpose of this paper is to explore the role of key indicators of agriculture advancement in the state of Gujarat. Design/ Methodology/ Approach: The present study is an analytical as well as descriptive study. Research limitations/ implications: The study has explored contribution of technological advancement, impact of sustainability, and agriculture marketing as the important indicators of agriculture development in Gujarat. Originality/ Value: The paper has explored a positive relationship between Agri. GSDP of Gujarat state and factors affecting such as agriculture credit, gross irrigated area, use of NPK fertilizers and cropping intensity, whereas the relationship between dependent variable (Agri, GSDP) and one of the independent variable (rainfall) are less correlated.